Control of adeno-associated virus type 2 cap gene expression: relative influence of helper virus, terminal repeats, and Rep proteins. - Weger, S (1997)
Adeno-associated virus type 2 (AAV-2) gene expression is tightly controlled by functions of the helper virus as well as by the products of its own viral rep gene. Double-immunofluorescence studies of Rep and VP protein expression in cells coinfected with AAV-2 and adenovirus type 2 showed that a large proportion of these cells expressed Rep78 and Rep52 but no capsid proteins. The percentage of Rep78/Rep52- and capsid protein-positive cells was strongly influenced by the relative ratio of AAV-2 to adenovirus type 2. In contrast, nearly all cells positive for Rep68/Rep40 were also positive for capsid protein expression. Examination of p40 promoter transactivation by individual Rep proteins in the presence of adenovirus, however, showed that both Rep78 and Rep68 efficiently stimulated p40 mRNA accumulation and capsid protein expression. This strong transactivation was reliant upon the presence of terminal repeats and correlated with template amplification. In replication-deficient expression constructs, transactivation was observed only with Rep68 and was dependent on the linear Rep binding site within the left terminal repeat which was detected in the presence of high adenovirus concentrations. In the absence of any terminal repeat sequences, Rep68 expression again led to a minor transactivation of capsid protein expression which was detectable only at low adenovirus concentrations. This low level of transactivation of capsid protein expression by Rep proteins in the absence of terminal repeats resulted in a lower efficiency of capsid assembly. The data show a dominant influence of adenovirus type 2 functions on AAV-2 gene expression, a requirement for terminal repeats for strong transactivation of the p40 promoter by Rep proteins, and differential influences of Rep78 and Rep68 on AAV-2 promoters. Implications for the production of recombinant AAV-2 vectors are discussed.